Short Vi-polysaccharide abrogates T-independent immune response and hyporesponsiveness elicited by long Vi-CRM197 conjugate vaccine - Micoli, F; Bjarnarson, SP; Arcuri, M; Aradottir Pind, AA; Magnusdottir, GJ; Necchi, F; Di Benedetto, R; Carducci, M; Schiavo, F; Giannelli, C; Pisoni, I; Martin, LB; et al. (National Academy of Sciences, 2020)
Polysaccharide-protein conjugates have been developed to overcome the T-independent response, hyporesponsiveness to repeated vaccination, and poor immunogenicity in infants of polysaccharides. To address the impact of polysaccharide length, typhoid conjugates made with short- and long-chain fractions of Vi polysaccharide with average sizes of 9.5, 22.8, 42.7, 82.0, and 165 kDa were compared. Long-chain-conjugated Vi (165 kDa) induced a response in both wild-type and T cell-deficient mice, suggesting that it maintains a T-independent response. In marked contrast, short-chain Vi (9.5 to 42.7 kDa) conjugates induced a response in wild-type mice but not in T cell-deficient mice, suggesting that the response is dependent on T cell help. Mechanistically, this was explained in neonatal mice, in which long-chain, but not short-chain, Vi conjugate induced late apoptosis of Vi-specific B cells in spleen and early depletion of Vi-specific B cells in bone marrow, resulting in hyporesponsiveness and lack of long-term persistence of Vi-specific IgG in serum and IgG+ antibody-secreting cells in bone marrow. We conclude that while conjugation of long-chain Vi generates T-dependent antigens, the conjugates also retain T-independent properties, leading to detrimental effects on immune responses. The data reported here may explain some inconsistencies observed in clinical trials and help guide the design of effective conjugate vaccines.